Keputusan Pembelian Konsumen Gerai Makanan Cepat Saji Ditinjau dari Kualitas Produk, Persepsi Harga dan Iklan - Yuli Harwani; Fauziyah Fauziyah (Bina Nusantara University, 2020)
Western fast food restaurant recently becoming a solution in providing meal service for those who are busy, especially for workers, students. Fastfood considered favored for the decent taste and price. This study aims to investigate the customers’ decision on purchasing the product that is much affected by the product quality, perception on price and also advertisments. The data analysis is done for 170 closed questionaire form the McDonalds booth in Jakarta Barat using convience sampling method. The result of descriptive analysis showed that most of the customer visiting the booth is female, students and college students and in between the age of 15-21 years old. The data analysis method and the hypotheses test are utilized by Smart-PLS (Partial Least Square) to find out predictive linear relationship among the variables studied. The testing method is utilizing the Measurement Model (Outer Model) and structural model (inner model). Latent variable relationship test result indicates that prime decision on purchasing is significantly affected by perception on price. In addition, the product quality followed by advertising is significantly affected consumer purchasing decisions.